2014
DOI: 10.1016/j.yhbeh.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic–androgenic steroids and appetitive sexual behavior in male rats

Abstract: Anabolic-androgenic steroids (AAS) increase libido and sexual behavior, but the underlying behavioral mechanisms are unclear. One way AAS may enhance expression of sexual behavior is by increasing the willingness to work for sex. In the present study, sexually-experienced male rats received daily injections of testosterone at supraphysiologic doses (7.5 mg/kg in water with 13% cyclodextrin) or vehicle and were tested for appetitive sexual behavior measured by operant responding for access to an estrous female.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…However, the role of testosterone in improving sexual behavior is still under debate. Some researchers suggest that testosterone has little, if any, impact on sexual activity [ 16 18 ]. For example, Damassa et al [ 19 ] reported no correlation between circulating testosterone levels and male sexual behavior in normal active rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of testosterone in improving sexual behavior is still under debate. Some researchers suggest that testosterone has little, if any, impact on sexual activity [ 16 18 ]. For example, Damassa et al [ 19 ] reported no correlation between circulating testosterone levels and male sexual behavior in normal active rats.…”
Section: Discussionmentioning
confidence: 99%
“…; Hildebrandt, Heywood, Wesley, & Schulz, ). Expressions of aggression and violence have been shown to be unpredictable and context dependent and generally only encountered when triggered by a stimulus (Kim & Wood, ; Wallin et al, ). Altered judgement pathways could make users' behaviours less flexible and unable to adapt to changing situations (Wallin & Wood, ).…”
Section: Psychiatric Effectsmentioning
confidence: 99%
“…As sex also stimulates reward centres in the brain, anabolic androgenic steroid‐induced dysfunction of reward circuits is postulated to influence sexual behaviour. Anabolic androgenic steroids have been reported to increase sexual arousal and desire in human subjects and exhibit dose‐dependent stimulation of sexual behaviour in animals (Kim & Wood, ). Rat models have shown, however, that there is no associated increase in willingness to work for sexual reward (Kim & Wood, ).…”
Section: Motivators For Anabolic Androgenic Steroid Usementioning
confidence: 99%
See 1 more Smart Citation
“…These factors, in turn, are associated with increased sexual risk behaviors (Ariely and Loewenstein, 2006; Malow et al, 2001; Raffaelli and Crockett, 2003). However, it is also important to note that chronic use of steroids may not confer the same effects on sexual arousal (Kim and Wood, 2014), and may be a phenomenon exclusive to acute and/or infrequent users.…”
Section: Discussionmentioning
confidence: 99%